2015
DOI: 10.1074/jbc.m115.684977
|View full text |Cite
|
Sign up to set email alerts
|

Slow Off-rates and Strong Product Binding Are Required for Processivity and Efficient Degradation of Recalcitrant Chitin by Family 18 Chitinases

Abstract: Background:The role of slow off-rates of processive enzymes acting on recalcitrant polysaccharides is poorly understood. Results: Chitinase variants with high off-rates and weak product binding were inefficient in degradation of recalcitrant chitin. Conclusion: Slow off-rates and strong product binding are required for high efficiency and processivity. Significance: Knowledge of determinants of processivity aids to design better enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 80 publications
12
47
2
Order By: Relevance
“…Several studies have reported largely different values of the dissociation rate (30 -33). The k off from the chitin nanowhiskers was 0.012 Ϯ 0.002 s Ϫ1 , whereas the k off from the ␣-chitin after 10 min and 2 h of incubation was 0.0028 Ϯ 0.0003 and 0.0015 Ϯ 0.0005 s Ϫ1 , respectively (32). These values were much lower than those found in the present study and our previous study (37).…”
Section: Mechanism Of Smchia High-catalytic-activity Mutantcontrasting
confidence: 82%
See 2 more Smart Citations
“…Several studies have reported largely different values of the dissociation rate (30 -33). The k off from the chitin nanowhiskers was 0.012 Ϯ 0.002 s Ϫ1 , whereas the k off from the ␣-chitin after 10 min and 2 h of incubation was 0.0028 Ϯ 0.0003 and 0.0015 Ϯ 0.0005 s Ϫ1 , respectively (32). These values were much lower than those found in the present study and our previous study (37).…”
Section: Mechanism Of Smchia High-catalytic-activity Mutantcontrasting
confidence: 82%
“…In previous studies, the hydrolytic activity of SmChiA against crystalline chitin was found to decrease after the introduction of an alanine mutation into the aromatic residues inside the substrate binding cleft (W167A, W275A, or F396A). These mutants showed reduced levels of processivity on the crystalline chitin (11,32). On the other hand, interestingly, these mutants were found to outperform SmChiA WT in the hydrolysis of soluble chitin and soluble chitosan (11,12).…”
Section: Mechanism Of Smchia High-catalytic-activity Mutantmentioning
confidence: 97%
See 1 more Smart Citation
“…A key obstacle for an efficient utilization of lignocellulosic biomass is the substrate recalcitrance, manifested by, among other effects, a rapid slowdown of the enzymatic deconstruction of cellulose within minutes after the initial activity burst phase at low cellulose conversion (Cruys‐Bagger et al, ; Murphy et al, ; Praestgaard et al, ). The origin of the activity burst has been attributed to either the heterogeneous nature of the substrate and the changes of the substrate morphology in the course of hydrolysis (Beckham et al, ; Ganner et al, ; Grethlein, ; Peciulyte, Karlström, Larsson, & Olsson, ), or to the enzyme‐related phenomena, such as inactivation of cellulases due to irreversible nonproductive binding onto the cellulose (Cruys‐Bagger et al, , ; Kostylev & Wilson, ; Kurašin, Kuusk, Kuusk, Sørlie & Väljamäe, ). Although experimental evidence from studies employing either pre‐steady‐state measurements (Cruys‐Bagger et al, ; Olsen, Kari, Borch & Westh, ) or time‐resolved high‐resolution visualization techniques (Igarashi et al, ; Nakamura et al, ) provided significant insights regarding the quantitative understanding of cellobiohydrolase action, many fundamental questions still remain open.…”
Section: Introductionmentioning
confidence: 99%
“…, or to the enzyme-related phenomena, such as inactivation of cellulases due to irreversible nonproductive binding onto the cellulose Kostylev & Wilson, 2013;Kurašin, Kuusk, Kuusk, Sørlie & Väljamäe, 2015). Although experimental evidence from studies employing either pre-steady-state measurements or time-resolved high-resolution visualization techniques (Igarashi et al, 2011;Nakamura et al, 2014) provided significant insights regarding the quantitative understanding of cellobiohydrolase action, many fundamental questions still remain open.…”
mentioning
confidence: 99%